Higher Mushroom Consumption Is Associated with Lower Risk of Cancer: A Systematic Review and Meta-Analysis of Observational Studies. Issue 5 (16th March 2021) - Ba, Djibril M; Ssentongo, Paddy; Beelman, Robert B; Muscat, Joshua; Gao, Xiang; Richie, John P
Abstract: Mushrooms are rich in bioactive compounds. The potential health benefits associated with mushroom intake have gained recent research attention. We thus conducted a systematic review and meta-analysis to assess the association between mushroom intake and risk of cancer at any site. We searched MEDLINE, Web of Science, and Cochrane Library to identify relevant studies on mushroom intake and cancer published from 1 January, 1966, up to 31 October, 2020. Observational studies ( n  = 17) with RRs, HRs, or ORs and 95% CIs of cancer risk for ≥2 categories of mushroom intake were eligible for the present study. Random-effects meta-analyses were conducted. Higher mushroom consumption was associated with lower risk of total cancer (pooled RR for the highest compared with the lowest consumption groups: 0.66; 95% CI: 0.55, 0.78; n  = 17). Higher mushroom consumption was also associated with lower risk of breast cancer (pooled RR for the highest compared with the lowest consumption groups: 0.65; 95% CI: 0.52, 0.81; n  = 10) and nonbreast cancer (pooled RR for the highest compared with the lowest consumption groups: 0.80; 95% CI: 0.66, 0.97; n  = 13). When site-specific cancers were examined, a significant association with mushroom consumption was only observed with breast cancer; this could be due to the small number of studies that were conducted with other cancers. There was evidence of a significant nonlinear dose–response association between mushroom consumption and the risk of total cancer ( P -nonlinearity = 0.001; n  = 7). Limitations included the potential for recall and selection bias in case-control designs, which comprised 11 out of the 17 studies included in this meta-analysis, and the large variation in the adjustment factors used in the final models from each study. The association between higher mushroom consumption and lower risk of cancer, particularly breast cancer, may indicate a potential protective role for mushrooms in the diet. Abstract : Findings from this systematic review and meta-analysis of observational studies showed a significant association between higher mushroom consumption and lower risk of cancer.